The Concept Of Property Management In The Qur'an And Its Implications In Social Life (Thematic Study According To Al-Azhar Tafsir) - Sabila, Hasya; Ayatullah, Ayatullah; Suwarno, Suwarno; Soleh, Rahmat; Alfaruq, Ahmad Yasin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
Social inequalities, such as poverty, limited education access, and wealth disparity, often stem from unjust wealth management. Islam, through the Qur'an, offers comprehensive guidelines on acquiring, consuming, purifying, distributing, and protecting wealth to benefit society. While Islamic finance has been widely studied, research linking wealth management to social implications remains limited. This study analyzes wealth management concepts in the Qur'an based on Tafsir Al-Azhar by Hamka and examines their impact on social welfare. Using a qualitative, literature-based approach with thematic tafsir, the study explores relevant Qur'anic verses in a modern socio-economic context. Findings reveal five key aspects of wealth management: halal acquisition emphasizing justice and spiritual balance, moderate consumption avoiding excess and miserliness, purification through zakat to reduce inequality, distribution via charity and waqf to foster social solidarity, and wealth protection through financial planning and inheritance for future security. The study confirms that applying Islamic wealth management principles can help reduce social inequality, improve welfare, and promote economic justice. It contributes to Islamic economic theory while offering practice al guidance fo individuals and policymakers to manage wealth fairly and sustainably.